The Effect of Smartboard-Based Interactive Media on Learning Interest and Mathematics Achievement of Elementary School Students - Hastutik, Lilik Muji; Muhajir; Nuril Huda; Sri Yuni Hanifah (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2026)
Integrating digital learning media in primary education has become increasingly important to enhance student engagement and academic achievement, particularly in subjects that students often perceive as difficult, such as mathematics. Interactive technologies such as Smartboards provide dynamic visual and interactive learning environments that can potentially improve students’ interest and learning outcomes. This study aims to examine the effect of interactive Smartboard media on students’ learning interest and mathematics achievement among fourth-grade students at SDN Kebun 2 Kamal. The research employed a quasi-experimental design with a quantitative approach. The sampling technique used was saturation sampling, involving the entire population of 50 students from classes IV-A and IV-B. The research instruments consisted of a mathematics learning achievement test and a questionnaire measuring students’ learning interest. Data were analyzed using IBM SPSS version 21, including tests of validity, homogeneity, normality, and an independent samples t-test. The findings reveal a statistically significant improvement in both students’ interest and learning outcomes after the implementation of Smartboard-based instruction, with a significance value of 0.000 (p < 0.05). The results indicate that the use of Smartboard media effectively enhances students’ engagement and academic performance in mathematics. Therefore, Smartboard technology can be recommended as an alternative instructional medium to support the achievement of learning competencies in elementary mathematics education